Chemical profiling, antioxidant, and antimicrobial activities of the essential oil of Matricaria recutita (Chamomile) - Ram Prasad Baral; Rameshwar Adhikari; Achyut Adhikari (Bibechana, 2025)
Matricaria recutita, commonly known as chamomile, is extensively utilized in the pharmaceutical, cosmetic, and food industries for its medicinal and essential oil properties. Local people from the Karnali Province of Nepal use this plant against skin and vaginal infection by bacteria and fungi. This research focuses on extracting essential oil through hydro-distillation, followed by Gas Chromatography-Mass Spectroscopy (GC-MS) to identify its chemical constituents and antioxidant and antimicrobial activities against bacteria and fungi responsible for common skin infections. The GC-MS analysis of the essential oil from M. recutita identified eleven chemical components. The major constituents, with respective area percentages at retention times 37.16, 11.79, and 7.88 in the GC chromatogram, were -farnesene (46.56%), -bisabolol oxide-A (11.79%), and menthol (7.88%). Limonene, methyl salicylate, and -bisabolol oxide-B also constituted the lowest area percentages at 1.36%, 1.59%, and 1.62%, respectively. The essential oil exhibited significant antioxidant activity with IC50 = 0.1924 µL/mL. Additionally, the essential oil exhibited notable antibacterial activity against Staphylococcus aureus ATCC6538P and Candida albicans, displaying zones of inhibition measuring 10.64 mm and 14.44 mm, respectively. The broth method also revealed that the MIC is above the 250 mg/mL range and has more potential for inhibition.